2021
DOI: 10.1186/s12865-021-00467-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of glomerular IgM deposition in patients with lupus nephritis

Abstract: Background The aim of the study was to investigate the clinical relevance of IgM deposition in patients with lupus nephritis (LN) in a large cohort. Results 217 patients with renal biopsy-proven active LN were enrolled. The associations between glomerular IgM deposition and clinicopathological parameters were further analyzed. IgM deposition was positively correlated with glomerular C1q and C3 deposition moderately (r = 0.436, P < 0.001; r = 0.4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In human studies, low C4 and elevated C4d in an aHUS cohort with FHAA correlated with anemia and IgM on kidney biopsy 59 . In lupus nephritis, IgM independently contributes to C3 deposition, and those with the highest IgM staining and lowest FH levels show exacerbated proteinuria and depressed systemic C3 levels 82 . Additionally, IgM as opposed to IgG has been shown to be a more important complement stimulus in xenotransplantation 83,84 .…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, low C4 and elevated C4d in an aHUS cohort with FHAA correlated with anemia and IgM on kidney biopsy 59 . In lupus nephritis, IgM independently contributes to C3 deposition, and those with the highest IgM staining and lowest FH levels show exacerbated proteinuria and depressed systemic C3 levels 82 . Additionally, IgM as opposed to IgG has been shown to be a more important complement stimulus in xenotransplantation 83,84 .…”
Section: Discussionmentioning
confidence: 99%
“…Anemia symptoms in LN patients may be related to renal damage and the generation of autoantibodies ( 29 , 30 ), however, there is currently no in-depth research indicating a direct link between anemia symptoms and PLN. Recent research indicates that IgM deposited in LN glomeruli can activate the complement system, driving disease progression, and lower IgM levels in LN patients’ serum may be associated with more severe manifestations of the disease ( 31 ). LN patients may experience electrolyte and acid-base balance disturbances due to renal impairment ( 32 ), manifested by elevated serum Cl levels and decreased UPH.…”
Section: Discussionmentioning
confidence: 99%
“…S5 In addition, in patients with lupus nephritis, glomerular IgM contributes independently to glomerular C3 deposition. 8 In a murine model of complement-mediated glomerular injury, IgM was deposited linearly along the GBM and animals unable to produce IgM developed milder disease histologically. 9 In addition to supporting the concept that IgM binding is a specific process, the authors identified 2 IgM clones that deposit specifically along the GBM of animals with glomerulonephritis but do not bind within the capillaries of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%